Isolation of allithiamine from Hungarian red sweet pepper seed (Capsicum annuum L.) - Attila Biro; Ferenc Gál; Csaba Hegedűs; Gyula Batta; Zoltán Cziáky; Barna Peitl; László Stündl; Gyöngyi Gyémánt; Judit Remenyik (Heliyon, 2018)
A natural fat-soluble thiamine derivative, namely N-[(4-amino-2-methylpyrimidin-5-yl)methyl]-N-[(2E)-5-hydroxy-3-(prop-2-en-1-yldisulfanyl)pent-2-en-2-yl]formamide (allithiamine) has been identified only in garlic (Allium sativum) until now. Hungarian red sweet pepper (Capsicum annuum) was found as a new source of allithiamine. Extraction procedure and analytical method were developed for the isolation of allithiamine and a chemical synthesis of the compound was also developed. First solid-liquid extraction was performed with 96 % ethanol to isolate allithiamine from pepper seeds. Thereafter, solid phase extraction was applied from ethanolic extract using C18 cartridge to concentrate and purify samples for further analysis. The structure of the synthesized and the isolated compounds was verified by reverse phase HPLC, HPLC-MS, MALD-TOF MS and NMR. Furthermore, effect of allithiamine was investigated on streptozotocin-induced diabetic mice with neuropathy. The results show that neuropathic pain sensation is improved by allithiamine treatment similarly to benfothiamine.